2004
DOI: 10.1177/112067210401400209
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy Results for Diffuse Diabetic Macular Edema with and without Inner Limiting Membrane Removal

Abstract: In eyes with diffuse diabetic macular edema vitrectomy seems to be effective, but additional ILM peeling presented better results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 22 publications
0
43
1
3
Order By: Relevance
“…Stefaniotou et al [131] retrospectively analyzed the results obtained in 73 eyes treated with PPV with or without ILM peeling. BCVA gains could be observed in both groups, but a greater improvement could be seen in patients undergoing ILM peeling.…”
mentioning
confidence: 99%
“…Stefaniotou et al [131] retrospectively analyzed the results obtained in 73 eyes treated with PPV with or without ILM peeling. BCVA gains could be observed in both groups, but a greater improvement could be seen in patients undergoing ILM peeling.…”
mentioning
confidence: 99%
“…Commonly, the release of traction and the removal of vitreous humor to reduce cytokines and angiogenic factors are thought to stand behind the success of vitrectomy in diabetic patients [14][15][16]. To achieve this, induction of a posterior vitreous detachment appears to be of particular importance [19].…”
mentioning
confidence: 97%
“…Previous investigators reported a positive impact of pars plana vitrectomy in DME [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64]. Vitrectomy with removal of the premacular posterior hyaloid may resolve the DME and improve vision in patients who previously failed to respond to conventional laser treatment.…”
Section: Pars Plana Vitrectomymentioning
confidence: 99%
“…In the following years, numerous retrospective studies have shown the advantage of vitrectomy and removal of the posterior hyaloid on morphologic and functional results [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65]. Harbour et al [35], Pendergast [36] and Kaiser et al [39] evaluated the surgical results in patients with a thickened and taut posterior hyaloid membrane in combination with DME and stated that early surgical intervention may result in better visual outcome.…”
Section: Pars Plana Vitrectomymentioning
confidence: 99%